Lineage-specific Virulence Determinants of Haemophilus influenzae Biogroup aegyptius - Strouts,FR; Power,P; Croucher,NJ; Corton,N; van,Tonder A; Quail,MA; Langford,PR; Hudson,MJ; Parkhill,J; Kroll,JS; Bentley,SD (Emerging Infectious Diseases, 2012)
An emergent clone of Haemophilus influenzae biogroup aegyptius (Hae) is responsible for outbreaks of Brazilian purpuric fever (BPF). First recorded in Brazil in 1984, the so-called BPF clone of Hae caused a fulminant disease that started with conjunctivitis but developed into septicemic shock; mortality rates were as high as 70%. To identify virulence determinants, we conducted a pan-genomic analysis. Sequencing of the genomes of the BPF clone strain F3031 and a noninvasive conjunctivitis strain, F3047, and comparison of these sequences with 5 other complete H. influenzae genomes showed that >77% of the F3031 genome is shared among all H. influenzae strains. Delineation of the Hae accessory genome enabled characterization of 163 predicted protein-coding genes; identified differences in established autotransporter adhesins; and revealed a suite of novel adhesins unique to Hae, including novel trimeric autotransporter adhesins and 4 new fimbrial operons. These novel adhesins might play a critical role in host-pathogen interactions.